3 The virial equation of state - Trusler,JPM (Experimental Thermodynamics, 2000)
In one sense, being restricted to gases at low and moderate densities, the virial equation of state is of rather limited application. Nevertheless, it has the merits of a sound theoretical basis, a large database of experimentally-determined virial coefficients, and the ability to describe mixtures exactly. The relations set out in Table 3.2 may be used to express a wide range of thermodynamic properties of pure gases and mixtures in terms of the virial coefficients, their temperature derivatives and the heat capacity of the ideal gas. The virial coefficients may be obtained from experiment, from knowledge of the intermolecular potential-energy functions or from the principle of corresponding states. The relations between the virial coefficients and intermolecular forces is of real importance and has therefore been explored in detail. Equations (3.52), (3.54), and (3.55) may be used to determine B and C from u12 and Δu3 at temperatures where quantum corrections are unimportant. Quantum effects have also been considered above in sufficient detail to permit their calculation for the atomic and molecular systems of interest. Because such calculations can now be performed routinely, even for non-spherical molecules, it is perfectly feasible to represent the equation of state correct at least to the third virial coefficient by means of prescribed pair and triplet potentials. © 2000 Elsevier B.V. All rights reserved.